Improved survival to hospital discharge in pediatric in-hospital cardiac arrest using 2 Joules/kilogram as first defibrillation dose for initial pulseless ventricular arrhythmia. (August 2020) - Hoyme, Derek B.; Zhou, Yunshu; Girotra, Saket; Haskell, Sarah E.; Samson, Ricardo A.; Meaney, Peter; Berg, Marc; Nadkarni, Vinay M.; Berg, Robert A.; Hazinski, Mary Fran; Lasa, Javier J.; Atkins, Dianne L.
Abstract: The American Heart Association (AHA) recommends first defibrillation energy dose of 2 Joules/kilogram (J/kg) for pediatric cardiac arrest with ventricular fibrillation (VF) or pulseless ventricular tachycardia (pVT). However, optimal first energy dose remains unclear. Methods: Using AHA Get With the Guidelines-Resuscitation® (GWTG-R) database, we identified children ≤12 years with IHCA due to VF/pVT. Primary exposure was energy dose in J/kg. We categorized energy doses: 1.7–2.5 J/kg as reference (reflecting 2 J/kg intended dose), <1.7 J/kg and >2.5 J/kg. We compared survival for reference doses to all other doses. We constructed models to test association of energy dose with survival; adjusting for age, location, illness category, initial rhythm and vasoactive medications. Results: We identified 301 patients ≤12 years with index IHCA and initial VF/pVT. Survival to discharge was significantly lower with energy doses other than 1.7–2.5 J/kg. Individual dose categories of <1.7 J/kg or >2.5 J/kg were not associated with differences in survival. For patients with initial VF, doses >2.5 J/kg had worse survival compared to reference. For all patients ≤18 years ( n  = 422), there were no differences in survival between dosing categories. However, all ≤18 with initial VF receiving >2.5 J/kg had worse survival. Conclusions: First energy doses other than 1.7–2.5 J/kg are associated with lower rate of survival to hospital discharge in patients ≤12 years old with initial VF/pVT, and first doses >2.5 J/kg had lower survival rates in all patients ≤18 years old with initial VF. These results support current AHA guidelines for first pediatric defibrillation energy dose of 2 J/kg.